Transformation of Education to Welcome the Golden Generation Of Indonesia 2045 (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
The Golden Indonesia 2045 vision is driving Indonesia's transformation into a developed nation. In order to achieve this goal, education - the primary pillar of human development - is essential. Nonetheless, a number of issues still plague Indonesia's educational system, including insufficient infrastructure, irrelevant curricula, and inconsistent teacher quality. In order to create a golden generation that is capable, bright, and morally upright, this study attempts to develop a complete education transformation approach. This study identifies a number of crucial elements that must be taken into account in education transformation through literature reviews and policy analysis, including the creation of a competency-based curriculum, the application of efficient learning technologies, raising the caliber of teachers, and extending equitable access to education. This report also emphasizes how crucial it is for communities, schools, the government, and the commercial sector to work together to support educational transformation. It is anticipated that the findings of this study would aid in the creation of improved educational policy in Indonesia. This study also comes to the conclusion that enhancing teacher quality, utilizing technology, and cultivating 21st century capabilities must be the main goals of educational change. The secret to a successful transformation is competency-oriented evaluation, active learning strategies, and a pertinent curriculum. This report offers policy suggestions that can help Indonesia Emas 2045 achieve its goals, specifically by boosting educational investment, enhancing collaboration between the government, educational institutions, and communities, and promoting educational innovation.